Business Strategy and Competitive Advantage of Companies - Tukirin, Tukirin (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The purpose of this paper is to identify and describe the role of culture and strategic choices in achieving competitive advantage for companies. The research methodology uses a systematic literature review that includes international journals that discuss strategic management. From several journals, an analysis was carried out and a common thread was drawn to get a scientific understanding related to the topic and title of this article. The results of the study indicate that in doing business across countries, it is very necessary to understand the right culture so that the company's presence can be accepted by the community. Companies can achieve competitive advantage by applying the right strategy to the right industry structure or by combining strategies and resources. Companies can implement strategies as needed and do not have to imitate all strategies, for example, companies in Japan only apply Porter's two strategies, the most of which are overall cost advantages, while the second is differentiation, while others use the original Japanese strategy. Keywords: Business strategy, competitive advantage, and company